Využití Lee-Carterova modelu pro predikci střední délky života - Slavíček, Ondřej; Jindrová, Pavla (Univerzita Pardubice, 2013)
The ageing of the population is a problem of many European countries including the Czech Republic. This problem is related to two main factors, the increase of life expectancy and the decline of birth rate. Here, attention is given to the first factor. For the purposes of this article, Lee-Carter model, which is one of the models used for modelling of mortality, was chosen. The article details the calculation method of the Lee-Carter method coefficients and then makes an estimate of their values for the real data from the mortality tables of the Czech Republic from the years 1950-2009. This makes it possible to predict the development of specific mortality rates and consequently also the development of life expectancy. A prediction of life expectancy for men and women in the Czech Republic for the period 2010-2029 is also made in this article, 95% prediction interval for this period is determined, and already known life expectancy values are compared with the predicted values.
Prediction of life expectancy using the Lee-Carter model
Keywords: mortality; mortality rate; life expectancy; Lee-Carter model; prediction